1976
DOI: 10.1021/ac60366a016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical error analysis of derivative spectrometry for the quantitative analysis of mixtures

Abstract: An effort has been made to assess the potential utility of derivative spectrometry for the quantitative analysis of mixtures. Using a numerical simulation method based on pairs of overlapping Gaussian bands, we have determined the systematic and random errors of measurement methods based on the Oth, 1st, and 2nd derivatives of a number of band pairs of different height ratio, width ratio, and separation. Derivative methods were found to give the lowest total errors in most of the cases studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(87 citation statements)
references
References 4 publications
0
87
0
Order By: Relevance
“…For example, this implementation is commonly used in signal processing of spectroscopic data and referred to as derivative spectrophotometry. 44 Fig . 6 presents the numerical 2nd derivatives of the imaginary part of the dielectric function for various samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this implementation is commonly used in signal processing of spectroscopic data and referred to as derivative spectrophotometry. 44 Fig . 6 presents the numerical 2nd derivatives of the imaginary part of the dielectric function for various samples.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that, because of the closeness of the two overlapping spectra of the zinc and cadmium complexes, these spectra are not suf®ciently resolved to give two distinct peaks. For this reason, the zerocrossing method [26] was used to resolve the mixture. The heights h 1 and h 2 in the second-derivative spectrum of the mixture (Fig.…”
Section: Absorption Spectramentioning
confidence: 99%
“…Several spectrophotometric methods, such as derivative spectrophotometry, [1][2][3][4][5] ratio spectra derivative method, 6 ratio spectra derivative-zero crossing method, 7-9 DDRS-DS method [10][11][12][13][14] and double divisor-ratio spectra derivative-zero crossing method 15 have been reported in the literature and applied for ternary and quaternary mixtures. However, it was observed that the derivative spectrophotometry and ratio spectra derivative method provide a good analytical resolution of binary mixtures but these two methods do not give always desirable results for the analysis of ternary and quaternary mixtures.…”
Section: Introductionmentioning
confidence: 99%